A multiscale ocean modelling system for the central Arabian/Persian Gulf: From regional to structure scale circulation patterns. (5th March 2023) - Hanert, Emmanuel; Mohammed, Aboobacker Valliyil; Veerasingam, Subramanian; Dobbelaere, Thomas; Vallaeys, Valentin; Vethamony, Ponnumony
Abstract: The Arabian/Persian Gulf (hereafter, the "Gulf") is one the busiest and fastest changing sea in the World. Its circulation is primarily driven by the surface water inflow from the Sea of Oman and density-driven and wind-driven flows within the Gulf. The regional circulation in its central part, particularly around Qatar, could not be explored because of unavailability of measured current data and the coarse resolution opted for the entire Gulf modelling. In the present study, we developed a high-resolution ocean modelling system of the entire Gulf with a particular focus on Qatar coastal waters. The model uses an unstructured mesh with different resolutions ranging from ∼ 5 km in the open ocean to ∼ 150 m along the coast of Qatar and less than 40 m around artificial structures. The model results have been validated with in situ data collected off Qatar. It allows seamless simulations of hydrodynamic processes from the entire basin scale down to the scale of coastal structures. The study identifies seasonal variability in currents and eddies in the central part of the Gulf. It also suggests the existence of four prominent anticyclonic eddies in the Gulf of Salwa, south of Bahrain. At the structure scale, the flow is mostly tidally driven and can be intensified beyond 1 m/s through narrow passages such as between breakwaters or within artificial waterways. By explicitly representing the effect of ocean sprawl on the coastal circulation, our model has the potential to greatly improve the environmental impact assessment of coastal developments in the Gulf area. Highlights: The ocean circulation in the Arabian Gulf is simulated with a multi-scale ocean model. The model is validated with in situ velocity and elevation data collected off Qatar. Model simulations suggest strong eddy activity in the Gulf of Salwa, South of Bahrain. Artificial structures along the coast of Qatar locally intensify the coastal circulation.